AN ANALYSIS OF LANGUAGE SWITCHING USED BY TEACHER AND THE SEVENTH GRADE STUDENTS OF SMP IT FATHONA BATURAJA - Ayu Widyaningsih; Yentri Anggeraini (Journal of Language Education (JoLE), 2022)
The aim of this research was to determine types of code-switching that used by teacher during teacher and students` interactions in English class. This research used qualitative method and adapted from theory of Poplack (1980). The procedure to collect the data used video recording and transcription. Based on data, code switching was used to facilitate intractions. So, the students can easier understand of teacher’s explanation. The result of this research indicated that intra-sentential as the type of code-switching is the most dominated in learning process.